Globalisasi dan Tata Ekonomi Politik Baru: Studi Kasus Persebaran K-Pop di Amerika Latin - S.M., Dias Pabyantara (Global and Policy Journal of International Relations, 2014)
ABSTRACTK-Pop in the last decade evolved into a cultural phenomenon that grew into a global trend. Development of the K-Pop as global trends then contain some indication of K-Pop categorization as a model of global capitalism. The spread of the K-Pop has reached the global level with a range of distribution in every continent. K-Pop positioned consequences as global capitalism modelis not linearwithsocialismideology. This paper argue that the spread of K-Pop globally, has compromised capitalism with socialism in society domain through the spread of the K-Pop in the of regional Latin America case study. This paperfurther argues that the DemocraticSocialistideology in the region of Latin America simply stop to the state level. While the society in Latin Americafollowthe global trend interactively.Keywords: K-Pop, capitalism, socialism, global.DOI:https://doi.org/10.33005/jgp.v2i01.1979